Development of Artificial Intelligence Based Animated Video Learning Media on Thaharah Materials - Marcel Tri Wahyudi; Sri Murhayati; Muhammad Luthfi Hamzah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The purpose of this project is to create animated video learning materials for Thaharah materials (Major and Minor Hadats) using artificial intelligence (AI) and assess how well they improve students' learning outcomes. The research and development (R&D) process employed the ADDIE paradigm, which comprises the phases of Analysis, Design, Development, Implementation, and Evaluation. Thirty students from SMA Negeri 5 Pekanbaru's tenth grade participated. Descriptive statistics, the Kolmogorov–Smirnov normality test, the Paired Sample t-Test, and N-Gain analysis were utilized to examine the data collected from pretest and posttest learning outcome assessments. The results showed a 2.43-point improvement from the mean pretest score of 5.50 to 7.93 in the posttest. With significant scores of 0.122 and 0.200, respectively (p > 0.05), the pretest and posttest data were both found to be normally distributed by the normality test. The Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between students' results before and after utilizing the created medium. The N-Gain value of 0.69, which was categorized as moderate and near the high category, also demonstrated a notable learning improvement. These findings show that students' comprehension and performance in Thaharah (Major and Minor Hadats) can be improved by using AI-based animated video learning materials. The created media provides a cutting-edge, captivating, and technologically integrated educational tool that facilitates interactive teaching and satisfies the needs of education in the twenty-first century.